Efektivitas Program Kemitraan BTDC Dan Dampaknya Terhadap Pendapatan Dan Penyerapan Tenaga Kerja UMKM Di Kabupaten Badung - Wirawan, Made Yudha; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 10, Oktober 2015 (pp.1194-1327), 2015)
Bali Tourism Development Corporation (BTDC) implement a partnership program to provide credit support to the Micro, Small and Medium Enterprises (SMEs) in the Badung regency in order to improve economic activities, expansion of employment opportunities and improve people's lives. This study aims to determine the effectiveness of the Partnership Program Bali Tourism Development Corporation in Badung, and to determine the impact on the income and employment of SMEs in Badung. Data analysis tools using effectiveness analysis, data normality and that Wilcoxon tests. Results of the discussion showed the implementation of the partnership program is quite effective, partnership programs can increase the income of SMEs and increasing the employment of SMEs in Badung.
Keywords: Efektivitas, Pendapatan, Tenaga Kerja